From Complicit Journalism to Militant Journalism: Politicians as Media Critics and Strategic News Users in Contested Political Scenarios - Orchard-Rieiro, M (Associacao Brasileira de Pesquisadores de Jornalismo, 2024)
In this article we identify how critical discourses about the media and journalists are articulated on social media by political actors. We also analyze how such expressions of media criticism coexist with other strategic uses of news content in politicians social media repertoires. The argument is based on a qualitative analysis of media-related Twitter posts (N=2062), from the 50 most active politicians Twitter accounts in the month following the Chilean social uprising of October 2019. Our findings reveal that criticism of journalism came from both ends of the political spectrum, despite news about the protests being regularly shared and used as factual support for informing followers, position-taking, criticizing adversaries, and self-promotion. We discuss how these forms of politicians interactions with the news operate as challenges to the authority of journalistic work. © 2024 Associacao Brasileira de Pesquisadores de Jornalismo. All rights reserved.